Biochemical and Microbiological Analysis of Urine and Blood in Femaleswith Urinary Tract Infection in Waist Province - iqbal hanash dhefer; Hussam Sami Awayid; Anfal Jamal Ibrahim (Academic Science Journal)
Between January 2023 and April 2023, 150 female patients with urinary tract infection were enrolled in the study at AL-Suwaira General Hospital. Two sets of patients were created: fifty patients had Proteus urinary tract infection, and twenty-five patients did not have Proteus urinary tract infection. The results of a blood test and a urine analysis were examined in these two groups. Using the disk diffusion test, the isolates' pattern of antibiotic sensitivity was also established. According to our findings, the Proteus patients had proteinuria, cloudy urine, and a positive nitrite test result. Patients with Proteus frequently had urine specific gravity (p≤0.05), proteinuria, and cloudy urine, while non-Proteus patients frequently had these symptoms as well. Blood test findings did not significantly differ between Proteus and non-Proteus patients.  Proteus species were the most sensitive isolate, whereas Neisseria species were the least sensitive. Levofloxacin is the most effective antibiotic, and it exhibits resistance to Pencillin but limited sensitivity to Nalidixic acid. For both Proteus and non-Proteus urinary tract infection, an early etiological identification is essential in order to promptly administer the proper empirical antibiotic treatment. This is crucial for preventing long-term treatment, complications, irreversible kidney damage, and the severity and chronicity of the disease. These clinical and test results can help us diagnose urinary tract infection at an early stage before urine cultures reveal the causing agents, which may require several days for therapy.